Entrepreneurship Capacity of Farmers for Community Based Entrepreneurship - Nerisa Nunez Paladan (The Asian Journal of Technology Management (AJTM), 2021)
Abstract. United Nations recognizes the vital role of the local communities like farmers and highlights the significance of leveraging their potential to achieve the Sustainable Development Goals (SDGs) through capacitating the farmers with their entrepreneurship competency. The study assessed the level of personal entrepreneurial competencies of farmers towards community-based entrepreneurship engagement. Specifically, it determines which competencies they excel in, recognizes the differences of entrepreneurial competency in terms of gender, business experience, and educational attainment and its correlation to age. Furthermore, the framework was developed in implementing community-based entrepreneurship. Descriptive research was utilized; 206 farmers and are the respondents of this study; they were surveyed, and assessed the level of entrepreneurial competencies using the Personal Entrepreneurial Competencies (PEC) Questionnaire with fifty-five questions through Likert scale. Findings reveal that farmers have a moderate entrepreneurial competency it ranks first the risk-taking and goal setting as the least.  Farmer self-confidence increases as they age; male farmers are more persuasive, farmers with business experience have higher competency for opportunity-seeking and risk-taking, and farmers' competency differs in terms of their educational attainment. Developing a framework for implementing community-based entrepreneurship should focus on intensifying the entrepreneurial competency of farmers to realize the success of their community based-enterprise.Keywords: Entrepreneurial competency, community based-entrepreneurship, farmers, community-based-enterprises.